Nickel(II)-2,2′-Bipyridylamine System. I. Synthesis and Stereochemistry of the Complexes - Hurley, T.J.; Robinson, M.A. (Inorganic Chemistry, 1968)
The reaction of 2,2′-bipyridylamine (abbreviated BPAH) with divalent nickel salts results in the formation of several products, the type of which depends on the metal:ligand ratio and the coordinating ability of the associated anion. Thus, tetrahedral [Ni(BPAH)Cl2] and octahedral [Ni(BPAH)3] (ClO4)2 and [Ni(BPAH)2Cl2] have been isolated and characterized. In these complexes, dipyridylamine coordinates in a bidentate manner through the two pyridine nitrogens. Deprotonation of the amine at ambient temperature in butanol results in the conversion of the paramagnetic [Ni(BPAH)2Cl2] species into a six-coordinate polymeric material of the general formula Ni(BPA)2 where the deprotonated bipyridylamine moiety (ab¬breviated BPA) is coordinating in a tridentate manner with the amine nitrogen acting as a bridge. This polymer is cleaved quite readily by the action of water, pyridine, and, presumably, other complexing solvents. Deprotonation of [Ni(BPAH)-Cl2] at high temperatures in naphthalene or reaction of the deprotonated polymer with nickel(II) chloride, also at high temperatures, yields a red crystalline trinuclear complex of the molecular formula [Ni3(BPA)4Cl2]. Deprotonation of bis(2,2′-bipyridylamine)copper(II) chloride and bis(2,2′-bipyridylamine)palladium(II) perchlorate give the expected four-coordinate square-planar product. The deprotonated complexes of palladium, copper, and nickel are compared and corre¬lations are made between their ease of formation and the geometry and electronic arrangement of the central metal ion. © 1968, American Chemical Society. All rights reserved.
78 citations (Crossref) [2023-10-31]
Keywords: dept.che